Towards Prediction of HCV Therapy Efficiency. Issue 2 (2010) - Wasik, Szymon; Jackowiak, Paulina; Krawczyk, Jacek B.; Kedziora, Paweł; Formanowicz, Piotr; Figlerowicz, Marek; Błażewicz, Jacek
Abstract : We investigate a correlation between genetic diversity of hepatitis C virus population and the level of viral RNA accumulation in patient blood. Genetic diversity is defined as the mean Hamming distance between all pairs of virus RNA sequences representing the population. We have found that a low Hamming distance (i.e. low genetic diversity) correlates with a high RNA level; symmetrically, high diversity corresponds to a low RNA level. We contend that the obtained correlation strength justifies the use of the viral RNA level as a measure enabling prediction of efficiency of an established therapy. We also propose that patient qualification for therapy, based on viral RNA level, improves its efficiency.